Hydroponic Pest Control System with Internet of Things Application - Azahari, Ahmad Ibrahim; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2023)
Hydroponics is becoming increasingly popular because it allows for the production of fresh food closer to major cities. People want "safe" food that was grown in a responsible, sustainable way and is free of chemical pesticide residues. Many insects cause problems that far exceed the benefits of using pesticides responsibly. Pesticide use is discouraged and rarely necessary in hydroponic gardening. Insects have a variety of effects on our quality of life. To address the issue, a pest control system must be developed. Pest control systems assist users in controlling their hydroponic gardens in order to maximize crop production and prevent pest attacks. The system will include Internet of Things (IoT) capabilities to make it more user-friendly. Arduino IDE, as well as Wemos D1 microcontroller, is necessary to code the system in this paper. Furthermore, the consumption of this system has also been analyzed to ensure that the user is aware of their power usage. It is found that the total energy usage by the system is 136.4 watts. The daily energy consumption is 3.2736 kWh, while the monthly consumption is 98.208 kWh. Next, the total financial cost for the complete development of this project is RM 315.90. It is also an innovative target for low-cost systems and global sustainable development.